Patch composition, patch and preparation method thereof
By using a combination of crystal inhibitor, antioxidant and pressure-sensitive adhesive in the transdermal patch of Compound I, the problems of easy crystallization and cold flow of Compound I are solved, and higher stability and effectiveness are achieved, and the permeability and absorption of the drug are enhanced.
Patent Information
- Application Number
- CN202411731695.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
Compound I is prone to crystallization in transdermal patches, affecting the drug transmission and absorption rate. At the same time, transdermal patches are prone to cold flow, resulting in unstable patches and affecting the efficacy.
By using a combination of crystal inhibitor, antioxidant and pressure-sensitive adhesive, a patch composition of Compound I was prepared to improve the stability of the drug, avoid crystallization and cold flow, and enhance the effectiveness and safety of the patch.
The higher stability and effectiveness of Compound I patches are achieved, the drug precipitation and cold flow phenomenon is reduced, the drug permeability and absorption rate are improved, and the patch safety is enhanced.
Smart Images

Figure CN119564643A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of pharmaceutical preparations, and in particular relates to a patch composition and a patch and a preparation method thereof. Background Art
[0002] Compound I is an estrogen, which has two types, α and β. The α type has a strong physiological effect and is secreted by the granulosa cells of the ovarian follicles. It can prevent and treat menopausal disorders such as headaches, internal heat, sweating, osteoporosis, Alzheimer's disease, arteriosclerosis, hyperlipidemia, etc. caused by estrogen deficiency in women during menopause or after menopause. It has multiple routes of administration, such as oral, intravenous, and transdermal administration. Among them, the transdermal route is favored because it can avoid the first-pass effect of the liver and is easy to use.
[0003]
[0004] Because Compound I easily absorbs water and becomes a semihydrate (semihydrate has lower solubility and is therefore easy to precipitate crystals), Compound I is prone to crystallization during the preparation and storage of transdermal patches, affecting the permeability and absorptivity of Compound I in human skin. In addition, since transdermal patches are prone to cold flow, when transdermal patches are applied to the human body, the "black circle" phenomenon is prone to occur, which easily stains clothes, affects the curative effect of application, and causes the patient's compliance to deteriorate. Therefore, providing a patch composition and patch of Compound I that reduces or avoids drug crystallization, reduces cold flow, reduces irritation, and has better stability is a technical problem that needs to be solved in this field. Summary of the invention
[0005] The present invention provides a patch composition of compound I and a patch and a preparation method thereof. By using a crystal inhibitor, an antioxidant and a pressure-sensitive adhesive in combination, the stability of the drug in the patch composition of compound I is improved, drug precipitation is avoided, cold flow is reduced, and the patch of compound I containing the patch has higher effectiveness, stability and safety.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides a patch composition of compound I, comprising the following components by weight: 2-4 parts of compound I or a pharmaceutically acceptable salt thereof, 12-17 parts of ethyl oleate, 5-9 parts of isopropyl myristate, 1-5 parts of propylene glycol laurate, 2-10 parts of a crystal inhibitor, 0.01-0.5 parts of an antioxidant, and 66-81 parts of an acrylic pressure-sensitive adhesive, wherein compound I is as follows:
[0008] In some embodiments, in order to obtain better drug release and permeability, the acrylic pressure-sensitive adhesive is acrylic pressure-sensitive adhesive DURO-TAK 387-2054.
[0009] In some embodiments, in order to achieve a better crystal inhibition effect, the crystal inhibitor is povidone.
[0010] In some embodiments, in order to achieve a better stabilizing effect, the antioxidant is butylated hydroxytoluene.
[0011] In some embodiments, in order to achieve better crystal inhibition and stabilization effects, the weight ratio of the crystal inhibitor to the antioxidant is 8:1 to 500:1.
[0012] In some embodiments, the weight ratio of the crystal inhibitor to the antioxidant is 50:1 to 100:1.
[0013] In a second aspect, the present invention provides a method for preparing a patch composition, the preparation method comprising: performing a first mixing of Compound I or a pharmaceutically acceptable salt thereof, ethyl oleate, isopropyl myristate, propylene glycol laurate, a first solvent and a second solvent, adding a crystal inhibitor and an antioxidant to the first mixture for a second mixing, and adding an acrylic pressure-sensitive adhesive to the second mixture.
[0014] In some embodiments, in order to better stabilize the system, the first solvent is ethyl acetate and the second solvent is methanol.
[0015] In a third aspect, the present invention provides a patch, comprising a backing layer, a drug storage layer and a protective layer arranged in sequence, wherein the raw material for preparing the drug storage layer comprises the patch composition of compound I described in the first aspect of the present invention.
[0016] In a fourth aspect, the present invention provides a method for preparing a patch, the preparation method comprising: coating a patch composition of Compound I on a backing layer to form a drug storage layer with a backing layer; and compounding a protective layer on the drug storage layer to obtain the patch.
[0017] The patch composition and patch of Compound I provided by the present invention have the following advantages:
[0018] 1. The compounding of two crystal inhibitors, povidone and butylated hydroxytoluene, provides a patch composition and patch of Compound I that reduces or avoids drug crystallization, reduces cold flow, reduces irritation, and has better stability, thereby improving the effectiveness and safety of the drug;
[0019] 2. By selecting a specific type of pressure-sensitive adhesive, the permeability of compound I in the patch composition and the patch is enhanced, thereby improving the effectiveness of the drug. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The release rate and time variation diagram of the patches prepared in Examples 1-5 and the reference preparation;
[0021] Figure 2 The appearance diagrams of the patches prepared in Examples 4, 5, 6, 7, 10 and 11 are shown;
[0022] Figure 3 This is a comparison diagram of the crystallization of the patch prepared in Example 6 after being placed at 25° C. and 90% RH for 5 days (left) and 10 days (right);
[0023] Figure 4 This is a comparison diagram of the crystallization of the patch prepared in Example 7 after being placed at 25° C. and 90% RH for 5 days (left) and 10 days (right);
[0024] Figure 5 This is a comparison diagram of the crystallization of the patch prepared in Example 8 after being placed at 25° C. and 90% RH for 5 days (left) and 10 days (right);
[0025] Figure 6 This is a comparison diagram of the crystallization of the patch prepared in Example 9 after being placed at 25° C., 90% RH for 5 days (left) and 10 days (right);
[0026] Figure 7 This is a comparison diagram of the crystallization of the patch prepared in Example 10 after being placed at 25° C., 90% RH for 5 days (left) and 10 days (right);
[0027] Figure 8 This is a comparison diagram of the crystallization of the patch prepared in Example 11 after being placed at 25° C., 90% RH for 5 days (left) and 10 days (right);
[0028] Fig. 9 This is a comparison diagram of the crystallization of the patch prepared in Example 12 and the reference preparation after being left alone for 7 days;
[0029] Fig.10 This is a comparison chart of the cold flow of the patch prepared in Example 12 and the reference preparation after being applied to the human body for 7 days;
[0030] Fig.11 This is a comparison chart of the irritation of the patch prepared in Example 12 and the reference preparation after being removed from the human body after being applied for 7 days;
[0031] Fig.12 The in vitro transdermal penetration curve comparison diagram of the patches prepared in Examples 12, 17 and 18;
[0032] Fig.13 The figure is a comparison chart of the drug-time curves of the patch prepared in Example 12 and the reference preparation in human body. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0034] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0035] "Optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes instances where the event occurs and instances where it does not.
[0036] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0037] In the present invention, the features defined as "first" or "second" may include one or more of the features explicitly or implicitly, and are used to distinguish and describe the features, without distinction of order or importance. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0038] The reference preparation is Bayer, Climara, 7.6mg / 25cm 2 .
[0039] The original formulation of the reference preparation is shown in Table 1:
[0040] Table 1 Original formulation of reference preparation
[0041]
[0042] In the present invention, the in vitro release experiment adopts the following implementation scheme: use the paddle disc method and use the Huarong dissolution apparatus to conduct the experiment. Fix the patch with the paste-containing side facing up in the center of the large paddle disc; set the test temperature: 32°C ± 0.5°C; rotation speed: 85rpm; the dissolution medium is 800ml 40% ethanol (v / v). Take out all the receiving solution at 5, 10, 20, 30, 45, 60, 90, 120, and 180, respectively, and add an equal amount of constant temperature receiving solution. The receiving solution is filtered with a 0.45μm microporous filter membrane, and the subsequent filtrate is taken as the test sample solution. The average release rate of compound I is determined by HPLC to obtain a graph of the change in release rate versus time.
[0043] In the present invention, the in vitro transdermal experiment adopts the following implementation scheme: the preparation and the reference preparation are cut into 1.54 cm 2 The circular slices were tested using the LOGAN automatic transdermal diffusion instrument. The test temperature was set at 32°C ± 0.5°C; the speed was 600 r / min; the receiving area was 1.54 cm 2 ; The volume of the receiving chamber is about 12.5 ml; The rehydration mode is: Go to waste; All the receiving solution is taken out at 2, 4, 8, 12, 16, 20, 24, 36, 48, 72, and 96 hours and an equal amount of constant temperature receiving solution is added. The receiving solution is filtered with a 0.45 μm microporous filter membrane, and the filtrate is taken as the test sample solution. The cumulative permeation per unit area of compound I is determined by HPLC, and the cumulative drug permeation and time change graph is obtained.
[0044] In the present invention, the detection of related substances in the patch uses the following implementation scheme: the paste surface of the patch is placed in a 50ml conical flask. 10ml of methanol is accurately added, sealed and ultrasonicated for 40min, taken out and vibrated for 20min, 10ml of 50% methanol is accurately added, mixed, and the supernatant is filtered through a 0.45μm filter membrane after standing to room temperature, and the subsequent filtrate is taken as the relevant test solution. The raw material drug is weighed and placed in a 25ml volumetric flask. 12.5ml of methanol is added, the raw material drug is dissolved, the solution is clear and transparent, and 40% methanol is added to dilute to the scale to obtain the raw material related test solution. The content of related substances is determined by HPLC.
[0045] The content of the active ingredient (API) in the following examples is based on dry product or anhydrous product.
[0046] Example 1
[0047] Since the pressure-sensitive adhesive model of the reference preparation was unknown, the pressure-sensitive adhesive model was first screened after confirming that the penetration enhancer and the raw material were consistent with the reference preparation.
[0048] Table 2 Example 1 Prescription Table
[0049]
[0050] Compound I, ethyl oleate, isopropyl myristate, propylene glycol laurate, 4 g of ethyl acetate and 5 g of anhydrous methanol were first mixed, and an acrylate pressure-sensitive adhesive was added to the first mixture for second mixing. The mixture was stirred with a stirrer for 60 minutes, and then allowed to stand to completely defoam the solution.
[0051] 113.2g / m 3The solution is coated on a 0.115 mm thick release film with a coating thickness of 1000 μm, and the coating is dried in an oven at 80°C for 10 minutes. After drying and cooling, the backing film is laminated. The required area is cut using a cutter to obtain a patch.
[0052] The cut patches are immediately placed in paper-plastic-aluminum packaging bags for storage.
[0053] Example 2
[0054] Table 3 Example 2 Prescription Table
[0055]
[0056] The preparation method is the same as that of Example 1.
[0057] Example 3 Table 4 Example 3 Prescription Table
[0058]
[0059] The preparation method is the same as that of Example 1.
[0060] Example 4 Table 5 Example 4 Prescription Table
[0061]
[0062] The preparation method is the same as that of Example 1.
[0063] Example 5
[0064] Table 6 Example 5 Prescription Table
[0065]
[0066] The patches prepared in Examples 1-5 were subjected to in vitro release experiments. The experimental results are shown in Figure 1 As shown, the release of the preparations prepared in Example 4 and Example 5 is good, but from the appearance observation, the colloidal solution of Example 5 has better compatibility, so the acrylic pressure-sensitive adhesive DURO-TAK 387-2054 was selected.
[0067] Since the preparation prepared in Example 5 has a greater risk of crystallization, the type and dosage of the crystal inhibitor were further screened.
[0068] Example 6
[0069] Table 7 Example 6 Prescription Table
[0070]
[0071] Compound I, ethyl oleate, isopropyl myristate, propylene glycol laurate, 4 g of ethyl acetate and 5 g of anhydrous methanol were mixed for the first time, a crystal inhibitor was added to the first mixture for the second time, and an acrylic pressure-sensitive adhesive was added to the second mixture for the third time. The mixture was stirred with a stirrer for 60 minutes, and then allowed to stand to completely defoam the solution.
[0072] 113.2g / m 3 The solution is coated on a 0.115 mm thick release film with a coating thickness of 1000 μm, and the coating is dried in an oven at 80°C for 10 minutes. After drying and cooling, the backing film is laminated. The required area is cut using a cutter to obtain a patch.
[0073] The cut patches are immediately placed in paper-plastic-aluminum packaging bags for storage.
[0074] Example 7
[0075] Table 8 Example 7 Prescription Table
[0076]
[0077] The preparation method is the same as Example 6.
[0078] Example 8
[0079] Table 9 Example 8 Prescription Table
[0080]
[0081] The preparation method is the same as Example 6.
[0082] Example 9
[0083] Table 10 Example 9 Prescription Table
[0084]
[0085] The preparation method is the same as Example 6.
[0086] Example 10
[0087] Table 11 Example 10 Prescription Table
[0088]
[0089] The preparation method is the same as Example 6.
[0090] Embodiment 11
[0091] Table 12 Example 11 Prescription Table
[0092]
[0093]
[0094] The preparation method is the same as Example 6.
[0095] Table 13 Crystallization experimental data of the patches prepared in Examples 6-8
[0096]
[0097] The crystal inhibition effect of the preparations prepared in Examples 6 and 7 is relatively good at the same amount of crystal inhibitor. Although within the limit, as the amount of crystal inhibitor increases, the crystal inhibition effect of the preparation prepared in Example 10 is the best, but from the appearance observation, Figure 2 As shown, the colloidal solution of Example 6 has good compatibility, so Example 6 was selected as the subsequent screening prescription.
[0098] Since the preparation prepared in Example 6 had related substance risks in stability testing, Examples 12-19 further screened the types and amounts of antioxidants.
[0099] Example 12
[0100] Table 14 Example 12 Prescription Table
[0101]
[0102] Compound I, ethyl oleate, isopropyl myristate, propylene glycol laurate, 4 g of ethyl acetate and 5 g of anhydrous methanol were mixed for the first time, polyvidone and an antioxidant were added to the first mixture for the second time, and acrylic pressure-sensitive adhesive was added to the second mixture for the third time. The mixture was stirred with a stirrer for 60 minutes, and then allowed to stand to completely defoam the solution.
[0103] 113.2g / m 3 The solution is coated on a 0.115 mm thick release film with a coating thickness of 1000 μm, and the coating is dried in an oven at 80°C for 10 minutes. After drying and cooling, the backing film is laminated. The required area is cut using a cutter to obtain a patch.
[0104] Immediately put the cut patches into paper-plastic-aluminum packaging bags for storage.
[0105] Example 13
[0106] Table 15 Example 13 Prescription Table
[0107]
[0108] The preparation method is the same as Example 12.
[0109] Embodiment 14
[0110] Table 16 Example 14 Prescription Table
[0111]
[0112]
[0113] The preparation method is the same as Example 12.
[0114] Embodiment 15
[0115] Table 17 Example 15 Prescription Table
[0116]
[0117] The preparation method is the same as Example 12.
[0118] Example 16
[0119] Table 18 Example 16 Prescription Table
[0120]
[0121] The preparation method is the same as Example 12.
[0122] Table 19 Test results of related substances in the patches prepared in Examples 12-16
[0123]
[0124] The preparations prepared in Examples 12, 13, 15, and 16 have lower risks of related substances and better stability. At the same time, it was unexpectedly found that the compounding of polyvidone and butylated hydroxytoluene has the effects of prolonging crystal inhibition, reducing cold flow effect, and reducing irritation. The comparison of the crystal inhibition effect, cold flow effect after application, and irritation to the human body after application of Examples 12 and 13 is shown in Table 20. The comparison between Example 12 and the reference preparation is shown in Table 20. Fig. 9 , 10 , as shown in 11.
[0125] Table 20 Comparison of stability effects of Examples 12, 13, 15, and 16
[0126]
[0127] Embodiment 17
[0128] Table 21 Example 17 Prescription Table
[0129]
[0130] The preparation method is the same as Example 12.
[0131] Embodiment 18
[0132] Table 22 Example 18 Prescription Table
[0133]
[0134]
[0135] The preparation method is the same as Example 12.
[0136] The patches prepared in Examples 12, 17 and 18 were subjected to in vitro transdermal testing. The results are shown in Fig.12 shown.
[0137] Embodiment 19
[0138] To further illustrate that the present invention has better efficacy, clinical experiments were carried out using the preparation prepared by the prescription and process of Example 12. The experimental results are shown in Tables 22 and 23.
[0139] The clinical trial adopted a two-preparation, single-dose, crossover design: 14 healthy, postmenopausal female subjects were selected and randomly assigned to two groups for two cycles of testing. In the first cycle, subjects in group 1 took the test preparation (T), and subjects in group 2 took the reference preparation (R). In the second cycle, subjects in group 1 took the reference preparation (R), and subjects in group 2 took the test preparation (T), and the washout period between the two cycles was >7 half-lives.
[0140] The blood collection points are as follows: The first cycle blood collection points: 0h before administration (within the first 60min), 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, 48h, 54h, 60h, 66h, 72h, 96h, 120h, 144h, 168h (patch removed), 180h, 192h, a total of 22 blood collection points. In the first cycle, each participant needs to collect 22 tubes of venous blood (3mL / tube). The blood collection points in the second cycle are the same as those in the first cycle.
[0141] After a single dose, blood drug concentration-time data were collected, and the main pharmacokinetic parameters (such as AUC, Cmax) were statistically analyzed, and the Cmax and AUC of the test preparation (T) and the control preparation (R) were compared. The AUC of compound I was calculated by WinNonlin 8.3 software, and the Cmax was taken as the measured value. The Cmax and AUC of the test preparation (T) and the Cmax and AUC of the control preparation (R) were logarithmically transformed, and the geometric mean ratio was calculated.
[0142] The geometric mean ratios of compound I AUC and Cmax of the test preparation (T) and the control preparation (R) were analyzed to preliminarily determine the differences in absorption extent and absorption rate between the test preparation (T) and the control preparation (R).
[0143] Table 23 Comparison of average pharmacokinetic parameters of test preparation T and control preparation R
[0144]
[0145] Note 1: a is the median, b is the minimum, c is the maximum.
[0146] Table 24 Fasting pre-test equivalent results (N = 14)
[0147]
[0148] Fig.13 is the drug-time curve of the reference preparation and the test preparation in the subjects, Fig.13 It can be seen that the peak drug concentration C of the patch prepared in Example 12 is max The area under the drug concentration-time curve AUC is higher than that of the reference preparation, which indicates that the present invention achieves better drug penetration effect than the reference preparation with less penetration enhancer.
Claims
1. A patch composition, characterized in that The composition comprises the following components by weight: 2-4 parts of compound I or a pharmaceutically acceptable salt thereof, 12-17 parts of ethyl oleate, 5-9 parts of isopropyl myristate, 1-5 parts of propylene glycol laurate, 2-10 parts of a crystal inhibitor, 0.01-0.5 parts of an antioxidant, and 66-81 parts of an acrylic pressure-sensitive adhesive, wherein compound I is as follows:
2. The patch composition according to claim 1, characterized in that The acrylic pressure-sensitive adhesive is acrylate pressure-sensitive adhesive DURO-TAK 387-2054.
3. The patch composition according to claim 1, characterized in that The crystal inhibitor is povidone.
4. The patch composition according to claim 1, characterized in that The antioxidant is butylated hydroxytoluene.
5. The patch composition according to claim 1, characterized in that The weight ratio of the crystal inhibitor to the antioxidant is 8:1 to 500:
1.
6. The patch composition according to claim 1, characterized in that The weight ratio of the crystal inhibitor to the antioxidant is 50:1 to 100:
1.
7. A method for preparing the patch composition according to any one of claims 1 to 6, characterized in that: The preparation method comprises: first mixing compound I or a pharmaceutically acceptable salt thereof, ethyl oleate, isopropyl myristate, propylene glycol laurate, a first solvent and a second solvent, adding a crystal inhibitor and an antioxidant to the first mixture for second mixing, and adding an acrylic pressure-sensitive adhesive to the second mixture.
8. The method for preparing the patch composition according to claim 7, characterized in that: The first solvent is ethyl acetate, and the second solvent is methanol.
9. A patch, characterized in that: The patch comprises a backing layer, a drug storage layer and a protective layer which are arranged in sequence, and the raw material for preparing the drug storage layer comprises the patch composition according to any one of claims 1 to 6.
10. A method for preparing the patch according to claim 9, characterized in that: The preparation method comprises: coating the patch composition on a backing layer to form a drug storage layer with the backing layer; and compounding a protective layer on the drug storage layer to obtain the patch.